2021
DOI: 10.1136/archdischild-2021-321988
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three intraosseous access devices for resuscitation of term neonates: a randomised simulation study

Abstract: ObjectivesTo compare the success rates and ease of use of three intraosseous (IO) access devices used in term neonates.DesignA three-arm randomised controlled simulation study was conducted.SettingA simulation laboratory.ParticipantsSeventy-two paediatric residents completing their emergency department rotation as part of their residency training, and 20 paediatric specialists.InterventionUsing an animal bone model, the one-attempt success rate of the EZ-IO drill, the NIO-I needle and the Jamshidi needle was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Anatomical investigation in stillborns reported that the semi-automatic drill, although easier to use, demonstrated lower success rates than the IO needles in establishing IO access. A subsequent randomized simulation study on a on a neonatal bone model confirmed these results [ 6 ]. The principle of IO access is to insert a needle into the medullary cavity of a long bone.…”
mentioning
confidence: 75%
“…Anatomical investigation in stillborns reported that the semi-automatic drill, although easier to use, demonstrated lower success rates than the IO needles in establishing IO access. A subsequent randomized simulation study on a on a neonatal bone model confirmed these results [ 6 ]. The principle of IO access is to insert a needle into the medullary cavity of a long bone.…”
mentioning
confidence: 75%